Intellectual disability in higher education: Self-perceived training needs of university teachers - Corbí, Miguel; Tombolato, Monica; Bueno-Sánchez, Lidia; Hermans, Katrien; Valenti, Antonella; Garcés-Ferrer, Jorge; Straniero, Alessandra; Brojčin, Branislav; Mesquita, Cristina; Bonifácio, Evangelina; Martini, Berta; Rodriguez-Cano, Sonia; et al. (Specijalna edukacija i rehabilitacija, 2021)
Introduction. The inclusion of students with disabilities in higher education is a fundamental right recognised by the legal system since its recognition in the United Nations Convention on the Rights of Persons with Disabilities. However, the measures adopted by European countries to promote their incorporation are not always accompanied by parallel training actions that provide university professors with the necessary knowledge to incorporate people with intellectual disabilities into the classroom with the same guarantees and opportunities as people without intellectual disabilities. Objective. This paper aims to provide specific data on the self-perceived training needs of university teaching staff and thus lay the foundations for a specific training programme. Methods. A cross-sectional study was carried out by means of a survey designed to collect the teachers’ perceptions of their own competences and the effectiveness of their knowledge, as well as the importance they attached to some aspects of intellectual disability. The survey was administered to teachers in Serbia, the Netherlands, Portugal, Italy and Spain, with a total sample of 1009 teachers. Results. The results obtained showed that the perception of self-perceived competence in educational skills is dependent on three main factors: previous specific training, teaching experience with people with intellectual disabilities and own personal experiences. Conclusion. The present study demonstrated the concern and need of the teaching staff to obtain specific training on people with intellectual disabilities in higher education.